Chrysin inhibits foam cell formation through promoting cholesterol efflux from RAW264.7 macrophages. (October 2015) - Wang, Shuai; Zhang, Xue; Liu, Mingyue; Luan, Hong; Ji, Yubin; Guo, Peng; Wu, Chongming
Abstract Context: Chrysin, a natural flavonoid, has been shown to possess multiple pharmacological activities including anti-atherosclerosis. Objective: The effects of chrysin on foam cell formation and cholesterol flow in RAW264.7 macrophages were investigated in this work to explore the potential mechanism underlying its anti-atherogenic activity. Materials and methods: The inhibitive effect of chrysin on foam cell formation and cholesterol accumulation induced by oxidized low-density lipoprotein cholesterol (ox-LDL) was assessed by oil red O staining and intracellular total cholesterol and triglyceride quantification in RAW264.7 macrophages. The action of chrysin on cholesterol efflux and influx was tested by fluorescent assays. Real-time quantitative PCR was used to quantify the relative expression of cholesterol flow-associated genes and luciferase assay was applied to test the transcription activity of peroxisome proliferator-activated receptor gamma (PPARγ). Results: Chrysin dose dependently inhibited the formation of foam cells and prevented the enhanced cholesterol accumulation by ox-LDL. Treatment with chrysin (10 μM) significantly enhanced cholesterol efflux and substantially inhibited cholesterol influx. Simultaneously, chrysin significantly increased the mRNA levels of PPARγ, liver X receptor alpha (LXRα), ATP-binding cassette, sub-family A1 (ABCA1), and sub-family G1 (ABCG1), decreased scavenger receptor A1 (SR-A1) and SR-A2, and increased the transcriptional activity of PPARγ. Discussion and conclusion: Chrysin is a new inhibitor of foam cell formation that may stimulate cholesterol flow. Up-regulation of the classical PPARγ–LXRα–ABCA1/ABCG1 pathway and down-regulation of SR-A1 and SR-A2 may participate in its suppressive effect on intracellular cholesterol accumulation.